2008
DOI: 10.1080/03601270701700359
|View full text |Cite
|
Sign up to set email alerts
|

Young People's Images of Old Age in Chile: Exploratory Research

Abstract: According to gerontological thought, an important part of senior citizens' disabilities are products of their social exclusion rather than factors associated with their physical or mental health. How these exclusions come about was the purpose of the research reported in this article. The study was conducted among 682 Chilean university students using a semantic differential test. A generalized negative image on old age was observed. The conclusion is that social images of old age affect the well-being of pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 5 publications
0
8
0
4
Order By: Relevance
“…On the other hand, however, less positive attitudes among college students were also found. For example, Chilean and Peruvian college students held a somewhat negative image of old age (Arnold-Cathalifaud et al 2008;Löckenhoff et al 2009). Similarly, Israeli (Bodner and Lazar 2008) and Spanish (Zambrini et al 2008) college students were also found to have less positive perceptions about older people.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, however, less positive attitudes among college students were also found. For example, Chilean and Peruvian college students held a somewhat negative image of old age (Arnold-Cathalifaud et al 2008;Löckenhoff et al 2009). Similarly, Israeli (Bodner and Lazar 2008) and Spanish (Zambrini et al 2008) college students were also found to have less positive perceptions about older people.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studying college student populations is significant because they are about to enter the work force as educated professionals who are likely to encounter, participate, and impact aging policies and elder care in their professional work as well as their personal lives. It has been argued that social perceptions, attitudes, and images of old age may have a large impact on the well-being of the aged population in the society (Arnold-Cathalifaud et al 2008).…”
mentioning
confidence: 99%
“…Para lograr explorar los imaginarios que los jóvenes estudiantes de la Universidad de Granada tienen sobre la vejez y la presencia/ausencia de estereotipos, se decidió la utilización de una prueba del tipo diferencial semántico (Arnold-Cathalifaud, et al, 2008) que supera los criterios de fiabilidad (Alfa de Crombach: 0,836) y validez.…”
Section: Métodounclassified
“…Según los psicólogos chilenos Arnold-Cathalifaud et al 5,6,9,11 , el hecho de que los jóvenes tengan imágenes negativas y pesimistas sobre la vejez, no deja de ser también un importante problema para ellos mismos. Sus imágenes constituyen expectativas sobre sus propios futuros: los jóvenes también envejecerán y deberán enfrentar esa etapa con sus propios estereotipos, aquellos que hoy reproducen.…”
Section: Estereotipos Que Deben Enfrentar Los Adultos Mayoresunclassified
“…Se espera que los AM confirmen las expectativas negativas que se tienen de ellos, por lo tanto, se produce una relación discriminatoria hacia ellos. Además, la percepción colectiva sobre el AM conduce a una autopercepción que afecta su propia autoestima, es decir, esta dinámica finalmente incluye a los propios involucrados: los AM terminan representando las imágenes desfavorecidas sobre su etapa de vida y se comportan consistentemente con ellas 11 .…”
Section: Estereotipos Que Deben Enfrentar Los Adultos Mayoresunclassified